Zinc Fractions and their Availability to Wetland Rice in Acidic Soils of Assam - Binoy Kumar Medhi and Khagen Kurmi, Gayatri Goswami Kandali, Nirupoma Gogoi Barua, Anjali Basumatary (Journal of the Indian Society of Soil Science, 2016)
Distribution of various fractions of soil zinc (Zn) and their relationships with soil properties in rice growing soils of Assam were studied with twenty five geo-referenced soil samples (0-30 cm) with variable Zn status from rice growing areas of Assam, representing 3 major soil orders viz., Entisol, Inceptisol and Alfisol. The distribution of different forms of Zn in rice soils revealed that water soluble and exchangeable Zn (WSEx-Zn) fraction in soils ranged from 0.32 to 1.92, complexed Zn (COMP-Zn) from 1.46 to 4.5, amorphous sesquioxide bound Zn from 1.30 to 6.21, crystalline sesquioxide bound Zn (CBD-Zn) from 0.45 to 2.25 and residual Zn (Res-Zn) from 101.7 to 285.2 mg kg-1 with mean values of 0.87, 2.71, 2.92, 1.12 and 186.98 mg kg-1, respectively. Residual Zn was the dominant fraction among all Zn fractions studied, which ranged from 101.7 to 285.2 mg kg-1 and the mean value was 186.9 mg kg-1. The WSEx-Zn, COMP-Zn, amorphous sesquioxide bound Zn, CBD-Zn and Res-Zn constituted 0.45, 1.57, 1.62, 0.63 and 95.7 per cent of total Zn. Multiple regression of physicochemical properties of soil with different Zn-fractions showed the highest R2 value (0.616) with COMP-Zn. Multiple regression of different Zn fractions with plant parameters showed the highest contribution of WSEx-Zn to plant Zn concentration (76.7%), Zn-uptake (63.0%) and dry matter yield (36.1%) of rice. Path coefficient analysis of different Zn-fractions with Zn-concentration in rice plant showed the highest direct effect (0.5610) of WSEx-Zn on Zn concentration and indirect effect of COMP-Zn (0.3731) and amorphous sesquioxide bound Zn (0.2508) via WSEx-Zn. Significant positive correlation was also observed between WSEx-Zn and plant Zn uptake (r=0.668**), plant Zn concentration (r=0.647**) and drymatter yield (r=0.401*), suggesting that water soluble plus exchangeable Zn fraction is of great importance in Zn nutrition of lowland rice. Major portion of Zn was in the residual fraction which contributed very little to plant uptake. Significant positive correlation among WSEx, organic complex and amorphous sesquioxide bound Zn indicated that they are possibly in dynamic equilibrium with each other.